Pengembangan Multimedia Pembelajaran Berbasis Web Pada Mata Pelajaran IPA Kelas VIII SMP - Mahareni, Yolanda; Syafril, Syafril; Anugrah, Septriyan; Kurnia, Reni (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The lack of utilization of learning media is one of the factors in students' low understanding of the material discussed and students feel bored during the learning process. Science subjects are one of the subjects that have a high level of understanding, one of the materials is animal cells and plant cells, therefore multimedia learning can help visualize this concept so that it is easier for students to understand. This research aims to find out how the process of developing multimedia learning and find out the results of validity tests and practicality tests. The development used is Research & Development (R&D). with a development model, namely a 4D model consisting of define, design, develop and disseminate. The results of the data analysis showed that the media validity with validator 1 got an average result of 4.93 in the